Raising of horn fly haematobia irritans (L.) (diptera: muscidae) in laboratory by means of egg and larva inoculation - Lima, Luiz Gustavo Ferraz [UNESP] (2014)
Several studies have required Haematobia irritans (L.) raising in laboratory. The present study assessed two methods of inoculating immature forms of H. irritans to obtain adults. In 2007, 15 Nellore steers (Bos indicus) (L.) were used for the collection of feces free of anthelmintic treatment and flies to produce for eggs and larva. For method I, 30 eggs were incubated in square filter paper (5 × 5 cm) and deposited on bovine feces (500 g) where they were kept until hatching and spontaneous penetration of larvae (L1) into the fecal mass. After 24 h, eggs were analyzed under a stereoscope microscope (40×) for the number of larvae that instinctively penetrated the feces. In method II, larvae were obtained only by natural egg hatching. At birth, 30 larvae were collected and individually inoculated, directly onto the fecal plate by employing a moistened brush. The tests were carried out at controlled temperature (28˚C ± 2˚C) and saturated humidity (80%) until the emergence of flies with both methods. The number of emerged flies was considered in the result. Using method I, 276 (76.7%) flies emerged from 360 inoculated eggs, while using method II, 283 (78.6%) flies emerged from 360 inoculated larvae. There was no significant difference (P = 0.7821) between methods for the number of flies; however, the proportion between males and females by means of larva inoculation was different from 1:1 (P = 0.0146). Results indicated that both methods led to a satisfactory production of flies and egg inoculation provided an easier establishment.